2015
DOI: 10.1097/pec.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Emergency Department Discharge After Pediatric Interhospital Transport

Abstract: In this single-site study, children referred from outside EDs with lower pediatric volumes and staffed by nonpediatricians were more likely to be discharged from a children's hospital ED after transport. These transports may represent unnecessary resource use. Outreach education, shared staffing models, and telemedicine are potential methods to address unnecessary transfers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…However, transfers from these hospitals were less likely to be probably avoidable compared to facilities with no pediatric‐specific capabilities. This finding aligns with previous work that potentially avoidable transfers occur less commonly when patients are transferred from EDs staffed by physicians with pediatric training . Together, this body of work suggests that expanding local pediatric expertise and resources may reduce both overall transfers and probably avoidable transfers.…”
Section: Discussionsupporting
confidence: 86%
“…However, transfers from these hospitals were less likely to be probably avoidable compared to facilities with no pediatric‐specific capabilities. This finding aligns with previous work that potentially avoidable transfers occur less commonly when patients are transferred from EDs staffed by physicians with pediatric training . Together, this body of work suggests that expanding local pediatric expertise and resources may reduce both overall transfers and probably avoidable transfers.…”
Section: Discussionsupporting
confidence: 86%
“…Sometimes, pediatric patients and their families are subjected to lengthy and risky transports because of a systematic tendency to "over-triage" children because of the potential need for pediatric specialty services (75). In fact, the transfer of some pediatric patients to a pediatric referral center is often not necessary if there is a closer hospital with adequate pediatric capabilities, such as a pediatric ward or intermediate pediatric or neonatal intensive care unit (NICU) with pediatric expertise (76,77).…”
Section: Inpatient Care Unitsmentioning
confidence: 99%
“…One such factor that influences an ED's readiness to care for children is the volume of pediatric patients. 17 Previous studies have revealed that children transferred from lowervolume EDs are more likely to be discharged from the receiving ED 17,18 ; therefore, it is possible that more transfers from lower-volume EDs are potentially avoidable and that lower-volume EDs may be more likely to transfer children with all conditions. Accordingly, our objectives were to assess how the likelihood of definitive care has changed over time for pediatric patients presenting to the ED with 3 common conditions: asthma, croup, and gastroenteritis.…”
mentioning
confidence: 99%